The Ethics of Space Homelessness and Squatting in Urban England - Grohmann, Steph (HAU Books, 2020)
Across the Western world, full membership of society is established through entitlements to space, formalized in the institutions of property and citizenship. Those without such entitlements thus become less than fully human, as they struggle to find a place where they can symbolically and physically exist. The Ethics of Space is an unprecedented account from an anthropologist who accidentally found herself homeless, studying what happens when homeless people organize to occupy abandoned properties. Set against the backdrop of economic crisis, austerity, and a disintegrating British state, Steph Grohmann describes a flourishing squatter community in the city of Bristol, and its eventual outlawing by this state. Contrary to a mainstream discourse that seeks to divide squatters into the 'deserving' homeless and 'undeserving' activists, Grohmann shows that squatters may in fact be homeless people who, choose to challenge property and the State.